تعريف حق الإجارة الطويلة وأسباب كسبها: دراسة تحليلية مقارنة - زينة غانم العبيدي; جاسم خضير الملا علي (PROSPECTIVE RESEARCHES, 2023)
The rent is an original right in rem of stipulated in Act (68) of the Civil Law, but it was not regulated, so he referred its rulings to the right of mediation. It has been dealt with by the comparative organizational laws, including Syrian, Lebanese, Moroccan and French laws, as well as islamic law. The most important thing that distinguishes this right: It's right in rem included with the property, it’s a formal right, a right not regulated by the Iraqi legislator, Temporary right. In addition to having a right range where the duration and type of land on which this right is based, as well as the type of updates, its duration may be up to 99 years, including all types of land, but the updated sought to include the facilities, construction and plantings, separately or in groups. As well as differing from the right of monopoly and that the right to long rent arises by contract and is subject to a certain configuration, which is registration where registration is in the department of registration as a corner of it. In addition to that it moves by will and the exercise and acquires the statute of limitations.